PAW37 Microarray analysis identifies the gene signature of spared vs vulnerable motor neurone groups. Issue 11 (22nd October 2010) - Wood, E; Heath, P; Shaw, P
Abstract : Motor neurone disease (MND) is characterised by the progressive degeneration of upper and lower motor neurones in the motor cortex, brain stem and spinal cord. However motor neurone groups such as those in the oculomotor nucleus are spared. This study aimed to investigate the differential gene expression profile of vulnerable and spared motor neurone groups, to give insight into the molecular basis of selective vulnerability of motor neurones in MND. Using human post mortem tissue from neurologically normal control cases, motor neurones from the lumbar spinal cord and oculomotor nucleus in the brainstem were extracted using laser-capture microdissection (Arcturus Pixcell II). The total RNA was isolated from the motor neurones and amplified. Biotin labelled antisense RNA was applied to Affymetrix U133 plus 2 GeneChips (DNA microarrays) and hybridisation washing and staining carried out to generate gene expression profiles. Key results were then verified by real-time quantitative PCR. Bioinformatic analysis was used to determine the biochemical pathways affected by differentially expressed genes. Both the microarray and the real-time PCR data showed a significant differential expression of genes. 589 genes were up regulated and 258 genes were down regulated (with a fold change of >2 and a p-value of <0.05) in oculomotor neurones compared to lumbar motor neurones. The genes up regulated in the oculomotor neurones indicate that this neuronal group may have an enhanced calcium handling capacity, altered ubiquitin mediated proteolysis, an altered balance of inhibitory and excitatory neurotransmission and different cytoskeletal components. This suggests that oculomotor motor neurones are indeed different in their behaviour to lumbar motor neurones, which may account for their reduced vulnerability during the disease process in MND.